1997
DOI: 10.1074/jbc.272.32.20269
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a Recombinant Substrate rAgg1 to Study the Biochemical Properties of Aggrecanase in Cell Culture Systems

Abstract: This paper describes the first report of the production and use of an artificial recombinant protein substrate to study "aggrecanase" activity. The substrate (rAgg1) is composed of the complete interglobular domain (IGD) of human aggrecan flanked by the "marker" sequences FLAG TM at the amino terminus and the human immunoglobulin G1 constant region at the carboxyl terminus. The expressed protein occurs as large multimolecular aggregates (>120 kDa) that, upon reduction, consist of a major isoform of 72 kDa (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 29 publications
3
38
1
Order By: Relevance
“…Other studies comparing the presence or absence of endogenous keratan sulfate chains have suggested that aggrecanase cleavage in the IGD may be increased in the presence of keratan sulfate and reduced when keratan sulfate is enzymatically removed (36,37). However, recombinant substrates that lack keratan sulfate are not totally resistant to cleavage by aggrecanases (38,39). Collectively, these studies suggest that keratan sulfate in the IGD may influence aggrecanolysis.…”
mentioning
confidence: 66%
“…Other studies comparing the presence or absence of endogenous keratan sulfate chains have suggested that aggrecanase cleavage in the IGD may be increased in the presence of keratan sulfate and reduced when keratan sulfate is enzymatically removed (36,37). However, recombinant substrates that lack keratan sulfate are not totally resistant to cleavage by aggrecanases (38,39). Collectively, these studies suggest that keratan sulfate in the IGD may influence aggrecanolysis.…”
mentioning
confidence: 66%
“…One caveat of studies with monolayer chondrocytes is that, to our knowledge, no one has been able to demonstrate production of soluble aggrecanase activity from these cells. For example, Hughes et al (37) have shown that an activity representing aggrecanase could be de- Figure 4. Effect of interleukin-1 (IL-1) and chondroitinase ABC (C-ABC) on immunolocalization of aggrecanase 1 (ADAM-TS4) in bovine articular chondrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The total amount of aggrecan loaded in each lane was 12.5 g. Native represents aggrecan substrate that has been pretreated with heat-denatured GAG digestion enzymes; Treated represents aggrecan substrate treated with keratanases (A) or chondroitinase ABC (B). Arrowheads in B indicate BC-3-reactive products with a higher molecular mass than in the control at 4 h. cleavage at the Glu 373 -Ala 374 bond by aggrecanase was detected using recombinant substrates lacking KS (28,34). These data suggest that the presence of KS is not an absolute requirement for cleavage at the Glu 373 -Ala 374 bond, but rather that the presence of KS may increase the efficiency of cleavage at this site.…”
Section: Discussionmentioning
confidence: 99%